m(6)A Methylation of Precursor-miR-320/RUNX2 Controls Osteogenic Potential of Bone Marrow-Derived Mesenchymal Stem Cells - Yan, Gege (Mol Ther Nucleic Acids, 2019)
Methyltransferase-like 3 (METTL3) is the main enzyme for N(6)-methyladenosine (m(6)A)-based methylation of RNAs and it has been implicated in many biological and pathophysiological processes. In this study, we aimed to explore the potential involvement of METTL3 in osteoblast differentiation and decipher the underlying cellular and molecular mechanisms. We demonstrated that METTL3 is downregulated in human osteoporosis and the ovariectomized (OVX) mouse model, as well as during the osteogenic differentiation. Silence of METTL3 by short interfering RNA (siRNA) decreased m(6)A methylation levels and inhibited osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) and reduced bone mass, and similar effects were observed in METTL3(+/−) knockout mice. In contrast, adenovirus-mediated overexpression of METTL3 produced the opposite effects. In addition, METTL3 enhanced, whereas METTL3 silence or knockout suppressed, the m(6)A methylations of runt-related transcription factor 2 (RUNX2; a key transcription factor for osteoblast differentiation and bone formation) and precursor (pre-)miR-320. Moreover, downregulation of mature miR-320 rescued the decreased bone mass caused by METTL3 silence or METTL3(+/−) knockout. Therefore, METTL3-based m(6)A modification favors osteogenic differentiation of BMSCs through m(6)A-based direct and indirect regulation of RUNX2, and abnormal downregulation of METTL3 is likely one of the mechanisms underlying osteoporosis in patients and mice. Thus, METTL3 overexpression might be considered a new approach of replacement therapy for the treatment of human osteoporosis.